Surgical repair of a meningoencephalocoele in a kākāpō (Strigops habroptilus). Issue 4 (26th May 2021) - Gartrell, BD; Argilla, LS; Chatterton, J; Dennison-Gibby, S; Digby, A; Fulton, J; Hunter, S; Johnson, KL; Jolly, M; Lenting, B
ABSTRACT: Case History: A kākāpō ( Strigops habroptilus ) chick hatched on an off-shore island of New Zealand with a small white mass protruding through the cranial skin of the head. The chick's growth followed a normal pattern for kākāpō but at 3 weeks of age the cranium mass was non-reducible and fixed in place and the chick was removed from the island for diagnostic imaging and hand-rearing. Clinical findings and treatment: A computed tomography (CT) examination revealed a full-thickness circular defect in the central cranium with suspected herniation of brain and dura. Surgery was performed at 37 days of age, and the herniated dura was dissected from the open fontanelle. Attempts to reduce the herniated tissue were unsuccessful, so the herniated dura and cortex were clamped and resected. The dura was closed and the periosteum of the skull was scarified and monofilament polypropylene mesh was secured tautly over the fontanelle. The mesh graft was infused with autologous bone marrow harvested from the ulna in an attempt to stimulate osteogenesis in the mesh repair. The skin flap was then closed. Post-operative recovery and healing were without complication. A CT examination 4 weeks after surgery showed no recurrence of the hernia, and a composite of mesh and scar over the open fontanelle which had reduced in diameter. The chick was released back onto an off-shore island with a radio transmitter and it continues to be monitored regularly. Pathological findings: The tissue resected at surgery consisted of a cylindrical core of cerebral parenchyma overlain by a mildly hyperplastic epidermis, and large amounts of oedematous fibrovascular tissue arising from the leptomeninges. Diagnosis: Rostral parietal meningoencephalocoele. Clinical relevance: This is the first report of successful surgical resolution of a meningoencephalocoele in any bird. Techniques from human neurosurgery were adapted for the unique anatomical features of the avian skull. The risks of the procedure included increased intra-cranial pressure resulting in anaesthetic complications or death, cerebrospinal fluid leakage, meningitis or recurrence of the meningoencephalocoele. In the longer term, there was a risk of developmental deficits in cognition or behaviour. None of these complications eventuated in the short to medium term, probably due to the small size of the meningoencephalocoele.